Social Security, Unanticipated Benefit Increases, and the Timing of Retirement - Burtless, Gary (Review of Economic Studies, 1986)
Between 1969 and 1972, real U.S. social security retirement benefits rose by 20%. The rise was unanticipated and followed over 15 years of relatively constant real benefits. This paper proposes a model of retirement behaviour in which workers respond differently, although in a theoretically consistent manner, to the anticipated and unanticipated components of the social security benefit they can receive upon retirement. The retirement age decision in the presence of unanticipated benefit changes is shown to be a special case of utility maximization under a nonlinear budget constraint. The model is estimated using the Longitudinal Retirement History Survey.